Accuracy of Meningitis Bacterial Score (MBS) as an indicator in establishing the diagnosis of acute bacterial meningitis in adults - Imas R. Palupi; Paulus Sugianto (Narra J, 2021)
Bacterial meningitis persists as a worldwide threat contributing to high mortality and morbidity rate, where differentiating bacterial meningitis from aseptic meningitis is key for better management and outcomes. Hence, this study aimed to assess the Bacterial Meningeal Score (BMS) as a tool for early diagnosis of acute bacterial meningitis. This study employed a retrospective cross-sectional method using medical records of patients with meningitis and meningoencephalitis who were hospitalized at Dr. Soetomo Hospital, from January 2018 to September 2021. Data of demographics, clinical, laboratory and cerebrospinal fluid (CSF) profile and culture were collected. The diagnostic performance of the BMS in diagnosing acute bacterial meningitis was evaluated by its sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (LR +) and negative likelihood ratio (LR -). A total of 128 patients who had been diagnosed with meningitis and meningoencephalitis were included. Out of total patients, 53 samples were diagnosed with acute bacterial meningitis as confirmed by CSF culture. The sensitivity and specificity of BMS with cutoff >2.5 in diagnosing acute bacterial meningitis were 92.4% and 92.0%, respectively with PPV 89.1% and NPV 94.5%. The area under the curve (AUC) of BMS in diagnosing of acute bacterial meningitis was 95.6% (95%CI: 92.3%, 99%). A BMS score of greater than 2.5 indicates a high likelihood of acute bacterial meningitis, whereas a score less than 2.5 indicates a low likelihood.